2000
DOI: 10.1042/0264-6021:3520037
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and gene organization of a human Neu5Acα2‒3Galβ1‒3GalNAc α2,6-sialyltransferase: hST6GalNAc IV

Abstract: On the basis of the detection of expressed sequence tag ('EST') similar to the rat N-acetylgalactosamine alpha2,6-sialyltransferase (ST6GalNAc) III cDNA, we have identified a novel member of the human ST6GalNAc family. We have isolated a cDNA clone containing an open reading frame that codes for a type II membrane protein of 302 amino acids with a seven-amino-acid cytoplasmic domain, an 18-amino-acid transmembrane domain and the smallest described catalytic domain of 277 amino acids. This predicted sialyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…Among these sialyltransferases, the ST6GalNAc IV gene was cloned and characterized from the human and mouse, but not from pig [3,11]. However, pig pST6GalNAc IV gene has only been reported from the NCBI Genebank database (GenBank accession number EU643700 and AJ620652).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Among these sialyltransferases, the ST6GalNAc IV gene was cloned and characterized from the human and mouse, but not from pig [3,11]. However, pig pST6GalNAc IV gene has only been reported from the NCBI Genebank database (GenBank accession number EU643700 and AJ620652).…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that human ST6GalNAc IV was expressed at low level in most human tissues and human cancer cell lines [11]. Furthermore, the mouse ST6GalNAc IV was specifically expressed in brain, colon and generally expressed in lung, thymus and spleen [3].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Given the ST6Gal-NAc4 high mRNA expression (Fig. 2e) and its restricted substrate specificity, recognizing only sialylated Galβ1-3-GalNAc O-glycans (sialyl T antigen) [18], it is likely that disialyl T antigens are expressed by monocytes and mo-DC.…”
Section: St Involved In α2-6-sialylation Of O-linked Chainsmentioning
confidence: 99%